MEMBANGUN PEMASARAN DIGITAL PADA UMKM AYRA BERKAH KERUPUK DI DESA KALIWADAS - Wahyu Prasetyawati, Aries Setyani; Firmansyah, Rendy; Awaludin, Muhammad Fajar (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
This Community Service Program (PKM) was implemented to improve the digital marketing capacity of the Ayra Berkah Kerupuk MSME located in Kaliwadas Village, Adiwerna District, Tegal Regency. This MSME was founded in 2006 and focuses on independently producing various types of crackers. Despite having a distinctive taste and a loyal customer base, product marketing remains limited because business owners do not yet understand optimal digital marketing strategies and do not yet have business legality. The objective of this activity is to assist partners in developing their business identity and utilizing digital platforms as promotional media. Methods used in this program include identifying partner needs, digital literacy training, and direct technical assistance. Forms of implementation include creating business logos and banners, training on the use of social media such as Instagram, Facebook, and TikTok, and creating a WordPress-based website as a digital storefront. In addition, the team also assisted in the legal process through the registration of a Business Identification Number (NIB). The results of the activity indicate that partners are beginning to understand the importance of visual imagery and digital promotion in expanding market reach. Partners are now able to manage social media accounts and websites independently. This program also had a positive impact on the students involved, improving their soft skills in communication, teamwork, and problem-solving in the field. Overall, the PKM program successfully empowered partner MSMEs through an educational and participatory approach to utilizing digital technology. Keywords: Digital marketing, crackers, legality, empowerment, MSMEs